O resultado da entrada das grandes redes de fast food para o município de Cubatão-SP no ano de 2024: como as grandes redes de fast food impactam os microempreendedores de Cubatão - FERNANDES, Maria Eduarda da Silva; COSTA, Maria Eduarda dos Santos; ATAIDES, Maria Eduarda Santos de; SANTIAGO, Rebeca dos Santos Matias; SILVA, Talita Coutinho da (181, 2024)
Sabe-se que as redes de fast food podem impactar os microempreendedores locais de diversas maneiras. Essas empresas têm uma vantagem competitiva superior aos pequenos empresários do setor, como por exemplo, recursos em marketing. Sendo assim, os pequenos negócios locais podem acabar sofrendo redução em seu faturamento, levando-os ao fechamento de seu estabelecimento.

It is known that fast food chains can impact local micro-entrepreneurs in several ways. These companies have a competitive advantage superior to small business owners in the sector, such as marketing resources. Therefore, small local businesses may end up suffering a reduction in their revenue, leading them to close their establishment.

It is known that fast food chains can impact local micro-entrepreneurs in several ways. These companies have a competitive advantage superior to small business owners in the sector, such as marketing resources. Therefore, small local businesses may end up suffering a reduction in their revenue, leading them to close their establishment.
The result of the entry of large fast food chains to the municipality of Cubatão-SP in 2024: how large fast food chains impact micro-entrepreneurs in Cubatão
Keywords: Consumo de alimentos; Planejamento estratégico; Varejo; Gestão e Negócios